1998
DOI: 10.1002/(sici)1096-9071(199805)55:1<28::aid-jmv6>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human monoclonal antibodies against hepatitis C virus envelope glycoproteins

Abstract: The isolation and characterization of human monoclonal antibodies (humAbs) against the hepatitis C Virus (HCV) glycoproteins E1 and E2 are described. B-cells from blood donors with anti-HCV were transformed with Epstein-Barr virus. The supernatants of the resulting lymphoblastoid clones were screened by ELISA with an extract of cells infected with a recombinant vaccinia virus RMPA95 expressing the envelope proteins E1 and E2 of an HCV genotype 1a virus (H strain). Positive clones were fused to the heteromyelom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The supernatants of the resulting lymphoblastoid clones were screened by ELISA with an extract of cells infected with a recombinant vaccinia virus, RMPA95, expressing the envelope proteins E1 and E2 of an HCV genotype 1a (H) strain. Positive clones were fused with the heteromyeloma line K6H6/B5 (14).…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants of the resulting lymphoblastoid clones were screened by ELISA with an extract of cells infected with a recombinant vaccinia virus, RMPA95, expressing the envelope proteins E1 and E2 of an HCV genotype 1a (H) strain. Positive clones were fused with the heteromyeloma line K6H6/B5 (14).…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, intracellular forms of truncated E2, enriched for the presence of monomeric, nonaggregated E2, were found to bind CD81 with greater affinity than the secreted forms (21,28), suggesting that structural differences exist between the intracellular and secreted forms of the E2 glycoprotein. Indeed, several monoclonal antibodies (MAbs) that recognize conformation-dependent epitopes within E2 have provided insight into the conformational state of the HCV envelope glycoproteins (5,9,12,15,16,26,27,38,43). Studies with these MAbs have demonstrated structural differences between truncated forms of E2 and full-length E1E2 complexes.…”
mentioning
confidence: 99%
“…Abs that arise in HCV-infected individuals in response to viral infection are anticipated to react with the truly native conformation of the viral envelope structure. Recently, several HMAbs have been identified that react with conformational epitopes within E2 (1,11,23,24). Moreover, some of these HMAbs have been shown to have neutralization-of-binding (NOB) activity (1, 23, 24) defined by their ability to neutralize binding of recombinant, truncated HCV-E2 to human cells (37).…”
mentioning
confidence: 99%